PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN UMKM BERBASIS LINGKUNGAN DI KELURAHAN BULAK BANTENG, SURABAYA - Nuroini, Indi; Istanti, Enny (LPPM Universitas Bhayangkara Surabaya, 2025)
Community empowerment is an important key to sustainable development, especially in urban-coastal areas that face economic and environmental challenges. This study aims to analyze community empowerment strategies through the development of environment-based MSMEs in Bulak Banteng Village, Surabaya. Using a descriptive qualitative approach with in-depth interview techniques, participatory observation, and Focus Group Discussion (FGD), this study explores changes in the perception and practice of MSME actors towards environmental issues. The results show that the direct involvement of the community in the empowerment process is able to increase awareness of sustainable business practices and encourage the adoption of environmentally friendly business principles, although still on a small scale. This research contributes to strengthening the theory of community empowerment and green entrepreneurship, as well as offering an effective collaborative approach to the development of MSMEs at the local level. These findings recommend the integration of environmental training and business assistance as a sustainable community empowerment strategy in the future.